Protein modifications and ionic strength show the difference between protein-mediated and solvent-mediated regulation of biomolecular condensation - Czajkowski, Artur; Udayabanu, Abhirami; Raj, Manthan; Pulibandla, Likhitha Ch. P.; Tursunović, Marija; Jahnel, Marcus; Adams, Ellen M. (Frontiers in Nanotechnology, 2025)
Biomolecular condensation is an important mechanism of cellular compartmentalization without membranes. Formation of liquid-like condensates of biomolecules involves protein-protein interactions working in tandem with protein-water interactions. The balance of these interactions in condensate-forming proteins is impacted by multiple factors inside of a living organism. This work investigates the effects of post-translational modifications (PTMs) and salt concentration as two such perturbing factors on the protein Fused in Sarcoma (FUS), an RNA binding protein. The protein was obtained from two expression systems differing by their capability to add PTMs to the protein, bacterial and insect cell. Attenuated total reflection Terahertz spectroscopy is used to probe the solvation behavior in condensates formed from FUS protein with and without PTMs at 100 mM and 2.5 M KCl. The results show that while PTMs impact the phase-separating propensity, they do not alter protein solvation in the condensate. On the other hand, salt concentration was found to alter the stiffness of the water hydrogen bond network. These findings have implications for biomolecular condensates chemistry, showing that condensate molecular organization is perturbed by fluctuations in solvent properties.